Determinant factors of service oriented organizational citizenship behavior among employees in a telecommunication company - Noor Hasnini, Kadim (2018)
The main purpose of this study is to identify the determinants factors of the organizational citizenship behavior in the service sector among Telekom Malaysia Kedah and Perlis employees. This study will determine the factors that affect attitudes of workers in the organization in providing services beyond their core responsibilities. Organizational citizenship behavior is a very important topic to be discussed as most of the employees whether in the government or private sector have been widely used it for task that beyond their responsibilities. The behavior of organizational citizenship in the services sector is a very important issues due to high demand in fulfill customer satisfaction. Every employees that are involved in the service sector needs to perform additional tasks beyond what is specified in the contract. Expected factors such as job satisfaction, motivation, job-related knowledge, organizational support, and organizational justice are essential to understand as all of these factors will affect the behavior of employees when performing services to the organization. In this study, data was collected through a quesionnaire survey from 254 respondents using simple random sampling method. The results suggested that job satisfaction, motivation, jobrelated knowledge, organization support, and organization justice had a significant relationship with service-oriented OCB. In addition, it was found that job-related knowledge is the most influential factor that contribute to service-oriented organizational citizenship behavior. In conclusion, organization should determine ways to increase employees’ service-oriented OCB so that they deliver excellent services.